A Model-Based Approach for Jump Analyses Regarding Strength and Balance - Hellmers, Sandra; Fudickar, Sebastian; Dasenbrock, Lena; Heinks, Andrea; Bauer, Jürgen M; Hein, Andreas (Biomedical Engineering Systems and Technologies, 2018)
To identify the functional decline as related to aging, geriatric assessments are an established instrument. Within such assessments, the functional ability is evaluated and consists of the three major components: strength, mobility, and balance. Counter movement jumps (CMJ) are well-suited to test these three essential elements of functional ability within a single assessment item. Since common balance measures have been shown to be significantly prone to algorithmic and technical variations, a robust alternative method is required. Thus, we introduce a model-based approach for balance and strength analyses, where the human lower extremities are modeled as an oscillating system during the phase of landing and recovery after a vertical jump. In the System and Control Technology, a transfer function of an oscillating system is described by a second-order delay element (PT2-element), which is characterized by the parameters natural frequency and damping. We analyze the jumps of 30 participants (70-87 years) regarding their jump phases and the mentioned parameters. A linear correlation between jump power and jump height, which are sensitive indicators of the muscle performance and the strength could be confirmed. While a correlation between jump power and spring constant could be observed, a significant relationship between the balance ability and natural frequency could not be identified.
Keywords: accepted; full paper; UNIAMT